Does Job Corps Work? Impact Findings from the National Job Corps Study - Schochet, Peter Z; Burghardt, John; McConnell, Sheena (American Economic Review, 2008)
This paper presents findings from an experimental evaluation of Job Corps, the nation's largest training program for disadvantaged youths. The study uses survey data collected over four years and tax data over nine years on a nationwide sample of 15,400 treatments and controls. The Job Corps model has promise; program participation increases educational attainment, reduces criminal activity, and increases earnings for several postprogram years. Based on tax data, however, the earnings gains were not sustained except for the oldest participants. Nonetheless, Job Corps is the only federal training program that has been shown to increase earnings for this population. (JEL I28, I38, J13, J24)